2013
DOI: 10.5455/gmj-30-2013-142
|View full text |Cite
|
Sign up to set email alerts
|

Allergy skin test results of an outpatient pulmonary clinic in Gaziantep

Abstract: Environmental factors play an important role in allergic sensitization. The aim of this study was to determine the spectrum of aeroallergen sensitivity of patients. The skin prick test results of patients with symptoms compatible with allergic diseases between March 2002 and December 2004 were retrospectively evaluated in Gaziantep University Pulmonary outpatient clinic. Of 1627 patients in whom skin prick tests (Stallergenes, France) were performed, 528 (32.5%) patients had at least one positive result among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These moulds are the most cosmopolitan fungi involved, particularly in temperate regions, due to their almost permanent presence in outdoor and indoor air (21). Cladosporium and Alternaria sensitivity has been reported at around 10% in the literature and 3% to 30% in European countries (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…These moulds are the most cosmopolitan fungi involved, particularly in temperate regions, due to their almost permanent presence in outdoor and indoor air (21). Cladosporium and Alternaria sensitivity has been reported at around 10% in the literature and 3% to 30% in European countries (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…We have found grass pollen (Phleum pratense) sensitivity in 94 (36.5%) asthmatic subjects. In the neighboring city of Gaziantep Bayram et al have reported the most common sensitivity to Phleum pretense (41.8%) and second most common allergy to Cockroach [12]. The difference between two studies might be due to study population and patient characteristics in which our study included only atopic asthmatics.…”
Section: Discussionmentioning
confidence: 85%